2002
DOI: 10.3727/096020197390022
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood Cells can be Induced to Express Markers for Neurons and Glia

Abstract: Rare cells are present in human umbilical cord blood that do not express the hematopoietic marker CD45 and in culture do not produce cells of hematopoietic lineage. These umbilical cord multipotent stem cells (UC-MC) behave as multilineage progenitor cells (stem cells) and can be expanded in tissue culture. Exposure to basic fibroblast growth factor (bFGF) and human epidermal growth factor (hEGF) for a minimum of 7 days in culture induces expression of neural and glial markers. Western immunoblots demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 19 publications
3
30
0
7
Order By: Relevance
“…This fi nding is consistent with a number of recent studies showing that undifferentiated human cord blood-derived stem cells appear to have very limited or no ability to undergo transdifferentiation after intracranial transplantation [36,37], although these cells appeared to be able to express a variety of glial and neuronal markers in vitro [9,10,12,38]. The fact that the surviving MSCs possessed lamin immunoreactivity implies these cells maintained some properties characteristic of the donor of origin but failed to transdifferentiate.…”
Section: Cord Blood-derived Msc Differentiationsupporting
confidence: 91%
“…This fi nding is consistent with a number of recent studies showing that undifferentiated human cord blood-derived stem cells appear to have very limited or no ability to undergo transdifferentiation after intracranial transplantation [36,37], although these cells appeared to be able to express a variety of glial and neuronal markers in vitro [9,10,12,38]. The fact that the surviving MSCs possessed lamin immunoreactivity implies these cells maintained some properties characteristic of the donor of origin but failed to transdifferentiate.…”
Section: Cord Blood-derived Msc Differentiationsupporting
confidence: 91%
“…The mononuclear hUCB cells that are cultured in specific conditioned media, including retinoic acid (RA) and nerve growth factor (NGF), expressed early neural markers such as musashi-1, nestin and neuronspecific class III beta-tubulin (TuJ1), mature neuronal markers such as neuronal nuclei (NeuN) and microtubuleassociated protein 2 (MAP-2) and astrocytic marker, glial fibrillary acidic protein (GFAP) [59]. Two different research groups Bicknese et al [60] and Buzanska et al [61] have also revealed that hUCB cells could differentiate into neural cell-like cells that express TuJ1, GFAP and galactosylceramide (GalC, oligodendrocytic marker). Especially, Buzanska et al [61] achieved neural stem cell-like cells using the CD34 − /CD45 − non-hematopoietic mononuclear cell fraction of hUCB.…”
Section: Transdifferentiation Into Neural Lineagesmentioning
confidence: 99%
“…In the last few years, there have been numerous studies demonstrating the plasticity of hUCB cells. These cells developed heterogeneous morphological characteristics atypical for hematopoietic-derived cells and express neural antigens in vitro (26)(27)(28), although it is not clear that their functional effects in vivo occur through this mechanism. Moreover, hUCB cells have been found to be effective in the treatment of animal models of stroke (29,30), traumatic brain (31) and spinal cord (32) injuries, and amyotropic lateral sclerosis (ALS) (33), probably providing protective trophic neuronal support by secretion of glialderived neurotrophic factor (GDNF) (34) or other growth factors.…”
Section: Introductionmentioning
confidence: 97%